Exploring the Sources of Influence in formation and Changing of Girls' Attitude towards the Consumption of Fashion Products - Pegu, Priyanka; Kumar, Brajesh (Indian Journal of Marketing, 2013)
The present study is a research paper based on the study conducted among college-going girls in Silchar town. The main aim of this paper is to explore the various sources of influence in formation and changing of college girls' attitude towards the consumption of fashion products. The nature of the study is both exploratory and descriptive research. The study was based essentially on the primary data captured through a specially designed questionnaire and was administered to a total of 248 respondents. In order to identify the sources of influence in formation and changing of college girls' attitude towards consumption of fashion products, the factorial analysis technique was considered appropriate. The results of factor analysis suggests that advertisements play the most significant role in determining college girls' attitude towards consumption of fashion products. As indicated by the results, the most suitable media to disseminate information pertaining to fashion products are Fashion magazines and Television. The college girls in Silchar town have easy access to local, national and international magazines, therefore, advertisements in fashion magazines act as an inspirational source for the college girls for the consumption of fashion products. However, the results of the study also suggest that Social groups, Direct experience and Direct marketing efforts are some other important indicators in determining college girls' attitude towards consumption of fashion products.